AB0276 Methotrexate therapy monitoring by MTOR, autophagy-related ULK1, caspase 3, CDK-inhibitor p21, TNF alpha, and osteoclast-specific cathepsin K and gelatinase MMP-9 gene expression in the peripheral blood of early rheumatoid arthritis patients. (23rd January 2014) - Tchetina, E.V.; Demidova, N.V.; Karateev, D.E.; Nasonov, E.L.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by synovial hyperplasia, mononuclear cell infiltration, bone erosion and joint destruction. Altered rates of cell proliferation and apoptosis were also observed in RA. We hypothesized that expression of the genes responsible for cell growth and proliferation (mTOR, p21), autophagy (ULK1), apoptosis (caspase 3), inflammation (TNFalpha), and bone resorption (cathepsin K and gelatinase MMP-9) measured in the peripheral blood could serve important biomarkers for anti-rheumatic therapy monitoring. Objectives: To find peripheral blood gene expression indicators pointing to treatment efficacy of methotrexate (MTX) in early RA patients. Methods: 14 early-stage seropositive RA females aged 44±16.0 years old, disease duration 9.0±6.5 weeks treated with MTX (17.5 mg) during two years and 47 healthy age-matched control females were examined in this study. Clinical response was assessed by disease activity score (DAS) 28, serum levels of anti-CCP antibodies, C-reactive protein (CRP), and rheumatoid factor (RF). Bone erosion and joint space narrowing scores were monitored by X-ray analysis. Total RNA isolated from the peripheral blood was used in gene expression studies performed with quantitative Real-time RT-PCR. p70-S6K, p21, and caspase 3 protein levels were quantified by ELISA. Results: Expression of all the examined genes measured in the peripheral blood was significantly upregulated (p<0.05) in RA patients compared to control at baseline. DAS 28 and CRP values have significantly decreased (p<0.05) at the end of follow up period. This was associated with significant downregulation of mTOR, p21, caspase 3, and cathepsin K gene expression, which attained the levels observed in healthy subjects. TNFalpha gene expression has also decreased (p<0.05) versus the baseline values. However it remained significantly higher than that in control subjects. In contrast, MMP-9 and ULK1 gene expression was significantly (p<0.05) upregulated in early RA patients compared to control in response to MTX therapy. This was accompanied by an increase in bone erosion numbers and joint space narrowing. Conclusions: Our results show that the examined gene expression measured in the peripheral blood could provide essential information for disease monitoring in RA in response to treatment. Moreover, blood levels of gelatinase MMP-9 and autophagy protein ULK1 gene expression might serve an important biomarker of treatment efficacy in respect to bone and joint integrity. Acknowledgments: This study was funded by Russian Foundation for Basic Research (project no. 09-04-01158-a and no. 12-04-00038-a). Disclosure of Interest: None Declared